Efektivitas Aver Viewer dalam Memantau Kemacetan Lalu Lintas di Kota Batu - Ilhami, Miranda Rista; Anugrah Santaufanny, Farah Fadillah; Sinambella, Rossa (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2020)
As a Tourism City, traffic congestion in Batu City continues to experience an increase. This encourages the Batu City Transportation Agency to create innovations in providing ease of service to road users. Along with advances in information and communication technology, the City of Batu Transportation Agency launched an application called Aver Viewer. The purpose of this study is to determine the effectiveness of Aver Viewer in monitoring traffic congestion in Kota Batu and whether the people of Kota Batu already know of this application. Effectiveness is a measure of success in achieving predetermined goals. The purpose of making the Aver Viewer application is considered to have been achieved, because this application makes it easier for the public to monitor congestion and find alternative routes to pass. This research uses descriptive research method with a qualitative approach. Data collection techniques used were questionnaire (questionnaire) and direct interviews to the Batu City Transportation Department and the community. The results of this study are that Aver Viewer is considered to be quite effective in monitoring traffic congestion in Batu City, with this application, it can facilitate road users to monitor traffic conditions without having to come directly to the field. But the lack of socialization carried out by the Department of Transportation about the Aver Viewer application caused the lack of people who knew of this application.